COMPARISON ANALYSIS OF RAILWAY BRIDGE MODUL FOR “I” GIRDER TYPE AND “WARREN” TRUSS TYPE - Dwi Agus Purnomo; Djoko Prijo Utomo; Agung Barokah Waseso; Mira Marindaa (BRIN, 2020)
The railway bridge in Indonesia, with a width of 1067 mm, was built in 1878, so that maintenance modules are needed to repair or to replace of construction modul at regular intervals. Implementation of maintenance and repairs refers to the Minister of Transportation Regulation No. 60 of 2012. Problems were encountered in the field at the BH182 Daop 2 railway bridge in Bandung due to lowering structural strength. Therefore, it was necessary to repair the bridge module with a new bridge design. The purpose of this study is to analyse and to calculate strength of the structure and to determine effectiveness of the use of construction materials on 2 alternative bridge construction selection with the type of “I